Modeling and controller design of pneumatic actuator system with control valve - Mohamed Yusoff, Norizam (2013)
Pneumatic actuators are very widely used in automatic production line now days because of it advantages. Pneumatic actuator offer several advantages over electromechanical and hydraulic actuator for positioning application such as clean operation, simple and easy maintenance and source of compressed air readily in almost industry plants. However, pneumatic actuators are subject to high friction force, deadband and deadtime which make fast and accurate position control difficult to achieved. This research project presents the process of controller identification design, modeling and control for pneumatic actuator. System Identification Toolbox is implemented in order to estimate the mathematical model of pneumatics for controller design. Behavior of the pneumatic actuator been observed if it can move at multiple location based on input given to the system. Data collection at input and output from the experimental work are used to estimate the model by selecting Auto Regressive Exogenous (ARX) model as model structure. Model estimation and validation are done by analyzing residual correlation and best fit percentage. PI controllers have been applied for controller design. The Effect of Tustin transformation and zero order hold and discrete model are tested in PI controller design. The results obtained in the experiment are successful to prove that the output signal which with controller are almost same for both simulation and experimental modes